PERANCANGAN APLIKASI PENGUKUR KADAR AIR PADA GETAH (KARET) BERBANTUAN ARDUINO UNO R3 - Busran; Jos Handreas (ITP Press, 2019)
Getah berasal dari getah sebuah pohon yaitu Pohon karet. Karet dapat menjadi sumber pertanian yang cukup banyak menopang roda perekonomian penduduk di Indonesia. Namun, dalam proses jual beli getah sangat tinggi tingkat kecurangan yang dilakukan petani dalam proses penjualan getah yang membuat harga getah murah. Harga mahal dan murahnya getah tergantung tingkat kandungan kadar air di dalamnya, semakin rendah kadar air pada getah maka semakin tinggi harga getah dan semakin banyak kadar air yang terkandung dalam getah maka semakin murah harga getah.Untuk itu penulis membahas tentang perancangan aplikasi pengukur kadar air pada getah berbantuan arduino dan sensor yang dipakai untuk pengukuran yaitu sensor soil moisture dan sensor load sell bekerja secara otomati suntuk pengecekan kadar air pada getah. Perancangan aplikasi pengecekan kadar air pada getah dilakukan 3 tahap yaitu perancangan hardware, perancangan software dan perancangan prototype. Perancangan hardware menggunakan sensor soil moisture untuk mengecek kadar pada getah, sensor load sell sebagai timbangan untuk mengukur berat getah, mikro kontroler arduino menggunakan bahasa pemograman C# dan ethernet shield untuk menghubungkan mikro kontroler dengan web server. Perancangan prototype menggunakan triplek tebal berukuran 30 x 30 untuk panampang timbangan dan sensor soil moisture diletakan pada penampang triplek. Berdasarkan hasil pengujian pengukur kadar air pada getah dapat melakukan pengukuran secara otomatis dan proses transaksi pengukuran kadar air pada getah tersimpan dalam database dan memiliki report dari data transaksi pengukuran kadar air pada getah. Sap comes from the sap of a tree that is rubber tree. The rubber can be a source of agriculture which propping up the wheels of economy Indonesian population. However, in the process of selling sap, there were very high level of deceit which was done by farmers in the process of selling the sap that makes the price of the sap becomes cheap. The expensive and cheap price of the sap, it depends on the level of moisture content in it. More low of the moisture content in the sap then the price of sap will be expensive and more high the moisture contain in the sap then the price of sap will be cheap. Therefore, the researcher discusses about designing applications for measuring moisture content in the sap (rubber) based on arduino and sensor which used for measurement namely soil moisture sensors and sell load sensor that works automatically for checking moisture levels on the sap. Application design for checking the moisture content in the sap performed in 3 stages: hardware design, software design and prototype design. Hardware design using soil moisture sensors to check the levels of the sap, sell a load sensor for measuring the weight scales of the sap, arduino micro controller using the C # programming language and the ethernet shield to connect the microcontroller to the web server. To display the measurement results of the prototype automatically and the data is stored into the database. Designing prototypes using thick plywood measuring 30 x 30 for longitudinal section of the scales and soil moisture sensors placed on the cross-section of plywood. Based on the test results of measuring the moisture content in the sap, can take measurements automatically and the transaction process measurements of the moisture content in the sap is stored in the database and have the report of the transaction data measuring the moisture content of the sap.